2020
DOI: 10.1186/s13104-020-05380-z
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth Experience Questionnaire (CEQ) in the Sri Lankan setting: translation, cultural adaptation and validation into the Sinhala language

Abstract: Objective To adapt the CEQ into Sri Lankan Sinhala cultural context and to determine the psychometric properties of CEQ. This would yield an opportunity to evaluate childbirth experience among Lankan population. Results Out of 390, 226 (57.9%) postnatal mothers completed the CEQ after 1 month postpartum. Face validity and content validity were demonstrated with all participants stating that CEQ was easy to understand and complete. For reliability, internal consistency was acceptable for the overall score (0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Other studies report adequate factor load values for the item [ 34 , 36 , 64 , 65 ]. This finding could not be compared in all studies since either they did not conduct factor analysis [ 32 , 40 , 42 ] or did not report factor loads obtained for the items [ 30 , 33 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies report adequate factor load values for the item [ 34 , 36 , 64 , 65 ]. This finding could not be compared in all studies since either they did not conduct factor analysis [ 32 , 40 , 42 ] or did not report factor loads obtained for the items [ 30 , 33 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these two items, the fit for the proposed four-domain model was good. Most published models for CEQ and CEQ 2.0 advocate for the existence of 4 factors-domains [ 30 , 31 , 34 , 36 , 41 43 , 45 ], although some studies propose models based on 3 factors-domains [ 35 , 64 , 65 ] or even 6 [ 33 ]. Most versions eliminate or make changes to the assignment of items to domains.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no tools have been validated in Sri Lankan setting to measure the RMC except for the Sinhala version of the Childbirth Experience Questionnaire. 38,39 A recent study from Colombo reporting the outcomes of person-centered maternity care has shown the poor-quality care across several domains of mistreatment during childbirth warranting broad health system reforms. 40 Only one previous qualitative study has evaluated obstetric violence in Sri Lanka, with a cohort of public health midwives (PHMs) and antenatal mothers, carried out as field research and the target HCPs were field PHMs.…”
Section: Importance Of Rmcmentioning
confidence: 99%
“…The scale was originally developed in Sweden in English language and is one among the scales that is considered valid and reliable to measure childbirth experience (26). Though, CEQ is not validated in India, it has been validated in various populations including South-Asian countries (27)(28)(29)(30)(31)(32).…”
Section: Childbirth Experience Questionnairementioning
confidence: 99%